2012
DOI: 10.1038/ijos.2012.61
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulatory mechanism of tooth root development

Abstract: The root is crucial for the physiological function of the tooth, and a healthy root allows an artificial crown to function as required clinically. Tooth crown development has been studied intensively during the last few decades, but root development remains not well understood. Here we review the root development processes, including cell fate determination, induction of odontoblast and cementoblast differentiation, interaction of root epithelium and mesenchyme, and other molecular mechanisms. This review summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
104
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 76 publications
(100 reference statements)
1
104
0
4
Order By: Relevance
“…1 The dental papilla differentiates into odontoblasts and forms dentin and pulp, and the Hertwig root sheath is associated with the number of roots and their morphology. 1,2 However, as with the mechanism underlying crown formation, the way in which root formation occurs has yet to be established.…”
mentioning
confidence: 98%
“…1 The dental papilla differentiates into odontoblasts and forms dentin and pulp, and the Hertwig root sheath is associated with the number of roots and their morphology. 1,2 However, as with the mechanism underlying crown formation, the way in which root formation occurs has yet to be established.…”
mentioning
confidence: 98%
“…The observed unsynchronized evolution therefore strongly suggests that changes in some of the genes coding for the shape of the crown did not result in change of the morphology of the roots of canine; this observation may mean that these genes do not code for the shape of the root. This hypothesis has already been proposed in other mammals (e.g., Shimizu 1995) and is supported by results on the molecular control of differentiation of odontoblasts and cementoblasts (Tummers et al, 2003;Huang et al, 2012).…”
Section: Relationship Between Root and Crown Evolutionmentioning
confidence: 61%
“…Some authors have suggested that SFRP4 modulates Wnt gene signals in the pregnant uterus (34). Wnt signaling is essential to tooth crown development, from initiation to the early bell stage, but Wnt expression is barely detectable during root development (2,35). SFPR4 might be associated with tooth root development via a Wnt signaling inhibitor.…”
Section: Discussionmentioning
confidence: 98%
“…HERS is associated with the number of roots and their morphology (2). The stem cells from the apical papilla appear to be the source of odontoblasts that are responsible for the formation of root dentin.…”
mentioning
confidence: 99%